Determinantes de la sostenibilidad y su relación con el alcance social en las microfinancieras peruanas 2015-2022 - Vallejos Burga, Jose Manuel (2023)
This paper investigates the determinants of the financial sustainability and the existence of the trade-off between this variable and the social outreach of Peruvian microfinance institutions for the period 2015 – 2022. In order to perform this analysis, it was used a static panel data, 6000 data and two measure models for sustainability and social outreach. In the first model, where operational self-sufficiency is the depended variable, the results suggest that administrative and financial expenses over actives have a negative and significant relation while the gross return on the portfolio and the loan portfolio has a positive and significant effect. In regard to the variables years in operation and GDP variation, these are not significant. In the second model, using return on equity as a proxy of sustainability, the results are similar, however, the loan portfolio in this second estimation is not significant. Finally, the results demonstrates that the trade-off between the studies variables do not exist. This goes against the theory but agrees with what is shown in the literature.